2012
DOI: 10.1103/physreve.85.061307
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of the structure of basin volumes for mechanically stable packings

Abstract: Experimental and computational model systems composed of frictionless particles in a fixed geometry have a finite number of distinct mechanically stable (MS) packings. The frequency of occurrence for each MS packing is highly variable and depends strongly on preparation protocol. Despite intense work, it is extremely difficult to predict a priori the MS packing probabilities. We describe a novel computational method for calculating the volume and other geometrical properties of the 'basin of attraction' for ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…3 (c)). We imagine that a one-dimensional trajectory L(φ, γ) through configuration space will encounter the basin of attraction [19] of a jammed packing with a probability F (φ)S(φ)dL during a step of size dL in configuration space, where S(φ) is the 2N − 1- dimensional cross-section of the basin of attraction of a jammed packing perpendicular to dL.…”
Section: Resultsmentioning
confidence: 99%
“…3 (c)). We imagine that a one-dimensional trajectory L(φ, γ) through configuration space will encounter the basin of attraction [19] of a jammed packing with a probability F (φ)S(φ)dL during a step of size dL in configuration space, where S(φ) is the 2N − 1- dimensional cross-section of the basin of attraction of a jammed packing perpendicular to dL.…”
Section: Resultsmentioning
confidence: 99%
“…The methodology as presented here is amenable to further development in several directions: (i) the regime 1 + 3/4 < H/σ < 2 of 32 tiles as identified in [14], (ii) mixtures of disks with different radii and masses including rattlers [35,36,37], (iii) spatial correlations of heterogeneities in mass density, and (iv) channels with the axis oriented vertically.…”
Section: Discussionmentioning
confidence: 99%
“…However, the approach of ref. [25] breaks down for higher dimensional systems for which most of the volume of the basin is concentrated at distances from the 'minimum' where the overwhelming majority of points do not belong to the basin. The method that we present here allows us to explore precisely those very rarified regions where most of the 'mass' of a basin is concentrated.…”
Section: Basins Of Attraction In High Dimensionsmentioning
confidence: 99%
“…Ashwin et al [25], defined the basin of attraction as the collection of initial zero-density configurations that evolve to a given jammed packing of soft repulsive disks via a compressive quench. On the basis of 'brute-force' calculations on low-dimensional systems, Ashwin et al suggested that basins of attraction tend to be "branched and threadlike" away from a spherical core region.…”
Section: Basins Of Attraction In High Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation